2016
DOI: 10.1080/0144929x.2016.1215525
|View full text |Cite
|
Sign up to set email alerts
|

Using virtual reality for industrial design learning: a methodological proposal

Abstract: Abstract. Nowadays, the different computer tools available enable designers to create complex industrial prototypes. The use of these tools is constrained by the limitations imposed by common devices, like screens and displays. Recently emerged Virtual and Augmented Reality techniques have started being used as supports in many learning and industrial environments. Beyond the new possibilities that these tools offer for designing industrial objects, the underlying question is whether these new technologies cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 22 publications
0
14
0
1
Order By: Relevance
“…However, most of these studies utilized VR in a nonimmersive form, relied on specific stationary simulators/hardware for training or did not consider immersive VR-interaction or cognitive demands (e.g. Alhalabi 2016;Jimeno-Morenilla et al 2016).…”
Section: Virtual Reality Training and Mental Workloadmentioning
confidence: 99%
“…However, most of these studies utilized VR in a nonimmersive form, relied on specific stationary simulators/hardware for training or did not consider immersive VR-interaction or cognitive demands (e.g. Alhalabi 2016;Jimeno-Morenilla et al 2016).…”
Section: Virtual Reality Training and Mental Workloadmentioning
confidence: 99%
“…They have measured the impact of this strategy on creative competence using the Abreaction Test of Creativity. The creativity is also focused on other the works [21,22]. Despite its relevance in autonomous learning and the skills of future engineers and designers, the enhancement of these qualities by virtual learning environments is not sufficiently contrasted.…”
Section: Introductionmentioning
confidence: 99%
“…Aspects such as fostering imagination and creativity are often overshadowed, especially as they are particularly difficult to measure objectively [24]. Precisely, to mitigate this lack of objectivity, the work of Jimeno-Morenilla et al [22], proposes the use of the Torrance test [25] to measure the impact of VR on students' creative capacity.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown that Virtual Reality can positively influence students' learning result in design (Allcoat and von-Mühlenen, 2018;Meyer et al, 2019;Radianti et al, 2020). For example, combining immersive VR with 3D modeling so that students could learn with a more intuitive and responsive process (Bruno et al, 2007;Jimeno-Morenilla et al, 2016;Liang et al, 2016;Camba et al, 2017;Hamurcu, 2018;Shih et al, 2019). VR technology could also help motivate the students in secondary school (Tang et al, 2020) and bring a new perspective to the course delivery.…”
Section: Introductionmentioning
confidence: 99%